รูปแบบองค์การที่มีสมรรถนะสูงของเทศบาลตำบล/High-performance Organization Model: The Subdistrict Municipality Case Study: The Subdistrict Municipality Case Study - ภูกองไชย, เขมณัฐ; พรหมเกิด, พรอัมรินทร์ (Journal of Humanities and Social Sciences (HUSOKKU), 2019)
Thailand has encountered economic and social crisis for a long time. One of the solutions the government selecting was the establishment of the local administrative organizations. The subdistrict municipality, one of the local administrative organizations, becomes like an important mechanism to solutions as it closes to the population and will be increasing in the future. However, while the subdistrict municipality has been doing duty to solve problems for the population, the performances of a subdistrict itself have been having many problems especially inefficient management. The problems have become an impediment to the subdistrict municipality’s ability. Therefore, the purpose of this research aims to study the factors of a high performance organization model for a subdistrict municipality in order to offer a high performance organization model. This research focused on administrative groups, employees, and the community in the subdistrict municipalities rewarded 1st, 2nd, 3rd prizes from ODLOC in fiscal year 2017. The approach was mixed-methods research. The data was collected by 502 questionnaires of the samples from three subdistrict municipalities in November 2018. Using the statistics of confirmatory factor analysis (CFA) found that the seven factors affected a subdistrict municipality’s proficiency to be a high performance organization. The five fit indices of the selected final model confirmed the model’s accuracy: /df=1.447, CFI=.970, NFI=.911, RMSEA=.055, and SRMR=.027. However, the findings suggested the items be modified. All factors obtained good validity and reliability: AVE=.658-789, CR=.843-.936, and Cronbach’s alpha=.882-.935. The quality-research part was a semi-structured interview. The results were consistent with those from the quantity research.